Nasionalisme, Demokratisasi, dan Sentimen Primordialisme di Indonesia: Problematika Identitas Keetnisan versus Keindonesian pada Studi Kasus Aceh, Papua, Bali, dan Riau - Rozi, Syafuan (Jurnal Penelitian Politik, 2009)
Ethnicity problem has been flaming the Indonesian political dynamics due to conflictual point of views between multiethnic and state position since Indonesian independence This problem is still unfinished Every region with its ethnichities expresses high demand of their symbolic political representative fair economic allocation and distribution of resources This article examines ethnicity problems in Aceh Papua Bali and Riau In Aceh and Papua cases coercive approach is used to achieve prosperity while Bali and Riau tend to use symbolic andpersuasive approach like Melayu people congress andAjeg Bali rising cores values to achieve fairness justice and sustainability This has been an on going process of rethinking and re evaluating of a biggest project of Indonesianess Keindonesiaan in a new way.